Contribuições da Educação Interprofissional ao ensino odontológico no Brasil: uma revisão sistemática - Dias, Karla Dias Castro (2020)
Interprofessional Education (IPE) occurs when two or more students of different professions share learning with each other, which results in improvement for the population's health condition. In dental education, significant changes have occurred in latest years. Therefore, it is important to analyze the characteristics of IPE experiences among dentistry students, and their contributions to dentist´s graduation. This is a systematic review of the literature about IPE in dental education in Brazil. The search for primary studies was conducted in English, Portuguese and Spanish in the databases: Lilacs, Scielo, BBO and Medline through the BVS; and in the repositories of dissertations and theses: Portal of Dissertations and Theses of Capes and BDTD. In addition, a manual search was conducted in the congresses proceedings of the Dentistry Schools in Brazil and ABENO meetings using the term “interprofessional” for publications from the last 10 years. The search was conducted by two researchers, independently, using the descriptors: health education, dentistry education, interprofessional education, collaborative interprofessional practice, interprofessional relationships, interprofessional collaboration and teamwork. It was selected publications of the last 10 years (experience reports, case reports, observational studies and comparative studies) that presented interventions related to the theme. The results indicated that the studies are mostly experience reports, requiring greater scientific evidence; PET-Saúde develop an important influence in IPE, there is a bigger involvement of public dentistry schools than private; the UBS represent the biggest scenario for the practice of IPE. The main benefits of the experiences consisted in the sharing of learning, appreciation of each professional, respect among professionals, deconstruction of stereotypes and awakening of new skills. Thus, it is concluded that IPE seems to contribute positively to the dentist´s graduation; the experiences show aspects that allow the consolidation of an integral vision of health and, consequently, improvement in assistance. This study verified a need for continued efforts by the dental community to investigate and apply IPE in Brazil